Pengaruh Financial Distress, Kepemilikan Institusional, dan Ukuran Dewan Direksi terhadap Ketepatan Waktu Penyampaian Laporan Keuangan : Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Kami Lia Mufida; Efrizal Syofyan (Universitas Negeri Padang, 2026)
Timeliness of financial report submission is one of the important qualitative characteristics that financial reports must fulfill, as timely information has higher predictive and feedback value for stakeholders. Delays in submitting financial reports can reduce information relevance and increase information asymmetry. In this research, three factors that can influence the timeliness of financial statement submission, including financial distress, institutional ownership, and board size.The objects of this research are property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Samples were obtained based on the purposive sampling method, resulting in 260 samples from 52 companies during the 2019-2023 period. The data analysis used in this research is logistic regression using SPSS 26 software.The findings of this research indicate that financial distress and institutional ownership do not have a significant influence on the timeliness of financial statement submission. However, board size has a significant positive influence on the timeliness of financial statement submission. This research contributes to strengthening previous research and identifying whether these factors have significant interactions in influencing the timeliness of financial statement submission.